Mode Optimization and Polarization Control in VCSELs with Sub-Wavelength Gratings - Yongli Wang; Chuanchuan Li; Yang Zhang; Jian Li; Xin Wei (IEEE Photonics Journal)
We have demonstrated the integration of sub-wavelength gratings (SWG) into a 795 nm vertical cavity surface emitting laser (VCSEL) with inverse surface relief to achieve coordinated control of the mode and polarization. At a grating period of around 0.5 μm and an etching depth range of 60 nm to 100 nm, the reflectivity was higher than 91%. A high reflectivity difference was introduced between different modes, effectively suppressing high-order modes with a side mode suppression ratio (SMSR) of 38 dB. The SWG exhibited different refractive indices for the transverse electric (TE) and transverse magnetic (TM) components, increasing anisotropy and thus enhancing the orthogonal polarization suppression ratio (OPSR) to 26.7 dB. The predesign and relaxed fabrication tolerances of grating parameters may facilitate the mass production of high-performance VCSELs for applications in quantum sensing systems.